O sagrado feminino de mim: uma poética cênica das mães ancestrais - MARTINS, Darciana de Fátima da Cruz (2019)
This work aimed to build a process of scenic poetic investigation, taking as reference the ancestral mothers of African and Afro-Brazilian matrices and the notion of Sacred Feminine Negro (RIBEIRO, 2017), possibilities and discoveries of the corporal construction of the archetypes of some pantheon energies feminine as: Yiamí Óssórón is the greater representation of the sacred feminine in these religions, and Nanã Buruku the matriarch and elder of these matrices. To do so, I construct my own corporeal narratives in a personal artistic process in dialogue with these sacred energies, establishing a direct and particular line with my ancestry, religiosity and, above all, my personality in the scenic construction of Ajê in me. Taking as a methodological reference the ethnocenology and articulating the concepts of Vianna (2005), Verger (1982), Mendes (2010), Foucault (1926), Ponty (1999). The study revealed that my creative process was the result of all the enchantments that I passed in the course of this research. I have achieved, as a result, relationships between my enchantments and the energies that I chose as a proposal of scenic creation, that is, I achieved in the process of creation the reflection of my own ways of life.